Climate change and range restriction of common salamanders in eastern Canada and the United States. Issue 5 (9th June 2022) - Widmer, Brian W.; Gehring, Thomas M.; Heumann, Benjamin W.; Nicholson, Kirsten E.
Abstract: The sensitivity of amphibian species to shifts in environmental conditions has been exhibited through long‐term population studies and the projection of ecological niche models under expected conditions. Species in biodiversity hotspots have been the focus of ample predictive modeling studies, while, despite their significant ecological value, wide‐ranging and common taxa have received less attention. We focused on predicting range restriction of the spotted salamander ( Ambystoma maculatum ), blue‐spotted salamander ( A. laterale ), four‐toed salamander ( Hemidactylium scutatum ), and red‐backed salamander ( Plethodon cinereus ) under future climate scenarios. Using bias‐corrected future climate data and biodiversity database records, we developed maximum entropy (MaxEnt) models under current conditions and for climate change projections in 2050 and 2070. We calculated positivity rates of species localities to represent proportions of habitat expected to remain climatically suitable with continued climate change. Models projected under future conditions predicted average positivity rates of 91% (89–93%) for the blue‐spotted salamander, 23% (2–41%) for the spotted salamander, 4% (0.7–9%) for the four‐toed salamander, and 61% (42–76%) for the red‐backed salamander. Range restriction increased with time and greenhouse gas concentration for the spotted salamander, four‐toed salamander, and red‐backed salamander. Common, widespread taxa that often receive less conservation resources than other species are at risk of experiencing significant losses to their climatic ranges as climate change continues. Efforts to maintain populations of species should be focused on regions expected to experience fewer climatic shifts such as the interior and northern zones of species' distributions. Abstract : We modeled the current and future climatic range distributions of 4 widely occurring North American salamander species (spotted salamander, blue‐spotted salamander, four‐toed salamander, and red‐backed salamander) in eastern Canada and the United States. We compared contemporary models with those projected under various climate change scenarios to estimate the loss or addition of climatically suitable habitat in 2050 and 2070.